2022
DOI: 10.1371/journal.pmed.1003900
|View full text |Cite
|
Sign up to set email alerts
|

Risks of specific congenital anomalies in offspring of women with diabetes: A systematic review and meta-analysis of population-based studies including over 80 million births

Abstract: Background Pre-gestational diabetes mellitus (PGDM) has been known to be a risk factor for congenital heart defects (CHDs) for decades. However, the associations between maternal PGDM and gestational diabetes mellitus (GDM) and the risk of specific types of CHDs and congenital anomalies (CAs) in other systems remain under debate. We aimed to investigate type-specific CAs in offspring of women with diabetes and to examine the extent to which types of maternal diabetes are associated with increased risk of CAs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 82 publications
(124 reference statements)
0
20
0
1
Order By: Relevance
“…Infants born to mothers with either GDM or PGDM have higher risks of having congenital anomalies, most frequently involving cardiovascular defects (Aberg et al, 2001;Moore et al, 2000;Spilson et al, 2001). A recent meta-analysis of population-based studies confirmed that the relative risks (RRs) of overall congenital anomalies in offspring of women with PGDM were higher than those in offspring of women with GDM (Zhang et al, 2022).…”
Section: Maternal Diabetes Mellitus and Ofcsmentioning
confidence: 99%
“…Infants born to mothers with either GDM or PGDM have higher risks of having congenital anomalies, most frequently involving cardiovascular defects (Aberg et al, 2001;Moore et al, 2000;Spilson et al, 2001). A recent meta-analysis of population-based studies confirmed that the relative risks (RRs) of overall congenital anomalies in offspring of women with PGDM were higher than those in offspring of women with GDM (Zhang et al, 2022).…”
Section: Maternal Diabetes Mellitus and Ofcsmentioning
confidence: 99%
“…GDM impairs cardiogenesis (Chaudhari et al, 2008; Dervisoglu et al, 2018), having a deleterious effect. It was estimated, through the available research, that infants born to mothers portraying GDM who needed insulin during the third trimester of pregnancy are around 20 times more likely to develop major anomalies regarding the cardiovascular system (i.e., malformations) than those born to non‐GDM mothers, with an absolute risk for infants from diabetic mothers around 9.7% (Becerra et al, 1990; Zhang et al, 2022, PMID: 35104296). Insulin‐binding cell receptors control fetal cardiac development and growth, being more abundant in the interventricular septum (Dervisoglu et al, 2018), regulating substrates needed for myocardial growth, therefore playing an essential role in physiological hypertrophy (Dale Abel, 2021).…”
Section: Know To Treat: Mechanisms Behind Cardiovascular Developmenta...mentioning
confidence: 99%
“…Chronic noncommunicable diseases (CND), like maternal arterial hypertension, diabetes mellitus (DM), and thyroids disease, could affect neonatal development (Ibrahim et al, 2022; Ogilvy‐Stuart & James, 2022; Ramakrishnan et al, 2015; Zhang et al, 2022). Acute infections of the TORCH complex (Toxoplasmosis, Rubella, Cytomegalovirus, and Herpes simplex virus) during pregnancy are related to congenital disorders, such as craniofacial, cardiopathies, and neural tube disease (NTD; Nayak et al, 2022).…”
Section: Introductionmentioning
confidence: 99%